2021
DOI: 10.1039/d1nr00453k
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free g-C3N4 nanosheets as a highly visible-light-active photocatalyst for thiol–ene reactions

Abstract: Thiol-ene click reactions are important for the construction of carbon–sulfur bonds. The use of visible-light photoredox catalysis for the formation of C–S bonds has attracted much attention. In this work,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The stability of the heterogeneous photocatalyst was examined by comparison of fresh catalyst and recycled catalyst. X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR) showed that the recycled catalyst did not change obviously in structure and morphology after five recycles (for details, see the Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…The stability of the heterogeneous photocatalyst was examined by comparison of fresh catalyst and recycled catalyst. X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR) showed that the recycled catalyst did not change obviously in structure and morphology after five recycles (for details, see the Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…73 Commonly, thiyl radicals were considered as the product of interaction between the photogenerated hole and bisulphide under visible light. 74 In this work, the consumption of Catalysis Science & Technology Paper photogenerated holes due to the production of thiyl radicals promotes the separation of photogenerated charge carriers, 75 which accelerated the accumulation of electrons at the surface reaction sites.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Unlike homogeneous catalysts, heterogeneous semiconductor photocatalysts have attracted attention because they are stable and reusable. Several metal oxides (TiO 2 , Bi 2 O 3 ), [20][21][22] chalcogenides (ZnIn 2 S 4 ), 23 and graphitic carbon nitride 24 have been employed as visible light photocatalysts for thiol-ene/yne reaction. Semiconducting TiO 2 has several benefits compared to other photocatalysts, such as being safe, readily available, cheap, and can be reused after filtration.…”
Section: Introductionmentioning
confidence: 99%